The Association between Coping Mechanisms and Depression in Patients with Chronic Kidney Disease Undergoing Hemodialysis at Dr. Moewardi Hospital Surakarta - Zweiryadinda, Wim; Oktaviyantini, Tri; Kusuma, Wijaya (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Patients with chronic kidney disease (CKD) undergoing routine hemodialysis (HD) may experience psychiatric comorbidities like depression. The coping mechanism is thought to be associated with the emergence of depression in patients with CKD. This cross-sectional study examines the association between coping mechanisms and depression in CKD patients undergoing routine HD therapy at Dr. Moewardi Hospital, Surakarta. Brief COPE and Hospital Anxiety and Depression Scale (HADS) questionnaire were used as study instruments. The result showed that 29 (78.38%) research subjects used adaptive coping, while 8 (21.62%) used maladaptive coping. There are 13 (35%) participants with mild depression. Spearman’s rank correlation showed a strong negative correlation between adaptive coping mechanisms and the severity of depression in CKD patients undergoing hemodialysis (r=-0,655; p<0,01)